In vitro antihyperglycemic and antioxidant potential of elettaria cardamomum l. Water and methanolic extracts - Ahmed, Afnan Sh.; Saxena, Anil Kumar; Ahmed, Qamar Uddin; Jamal, Parveen (2012)
Diabetes is a chronic common disease, prevalence of diabetes is increasing worldwide; this urges the need for more new treatment. Inhibition of intestinal alpha-amylase and alpha-glucosidase is an improtant strategy to control post-prandial hyperglycemia associated with type 2 diabetes mellitus. Based on the fact that plants have been the basis for the treatment of several diseases, Elettaria cardamomum L. (cardamom) has been selected for this study. It has been used traditionally to treat diabetes in Pakistan. Antioxidants present in plants can prevent the development of diabetes; hence, measurement of antioxidant activity of plants will also be carried out. The dried cardamom was extracted and dried extracts of the plant were examined for the alpha-glicosidase inhibition and pancreatic alpha-amylase inhibition. Extracts further quantified with respect to the total phenolic and flavonoid content. Our in vitro studies demonstrated a very good alpha-amylase inhibition %10.41 and %13.73 for water and methanolic extracts respectively. The total phenolic content (TPC) of the dried extracts were 11.99 and 6.46 mg GAE/g for water and methanolic extracts respectively. The total flavonoid content (TFC) is 21.02 and 20.55 QE/g for water and methanolic extracts respectively. We might say that our result can further support the view that some medicinal plants are promising sources of natural antidiabetic and antioxidants. These result support the use of this plant as a munching dietary supplement for the treatment of diabetes, and are first time report on the potential alpha-glicosidase and alpha-amylase inhibition in its activity.